DINAMIKA PEMEKARAN KECAMATAN PUCUK RANTAU KABUPATEN KUNTAN SINGINGI TAHUN 2005-2012 - Ahmad, Riza; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Ahmad Riza Formation Dynamics 1001120076 Regency Kuantan District of Overseas Shoots Singingi years 2005-2012. Supervising DR. Hasanuddin, M.Sc. Overseas Shoots Subdistrict is a district that has been expanded along with two other districts namely: SeberangHilirSubdistrict and District KuantanSentajo Kingdom. This division is set out in the Regulations Governing SingingiKuantan District No. 24 in 2012 In implementation dynamics that occur in the District Overseas Shoots this is the lack of expansion of its agreement made by the Government DistrickKuantanSingingi with government regulation No 19 of 2008 on the districts. That there was a violation of Article 4 (b) the organization of the village and the age limit of the number of villages are available expanded Overseas Shoots, but the division is still running with the arguments in the public interest.Overseas Shoots Subdistrict is the division of the sub-district parent KuntanMudik districts. So the theory is used to explain the dynamics of this problem is the Regional Expansion and Regional Autonomy which describes the dynamics of the early formation of the district, the need to meet the requirements of a district can be expanded up to the fight community and sub-district division teams get approval and endorsement of the district administration SngingiKuantan. So that in 2012 the Overseas Shoots districts legally become a new sub-district SingingidikabupatenKuantan. This division is done because of budget revenue for existing villages dikecamatan shoreline shoots are not able to build the facilities and good road infrastructure and development. This expansion can be felt so beneficial for rural communities to improve the economy and education for young Indonesian nation.Keywords: Dynamics of Expansion regional District and Regional Autonomy